Influence of the dynamical parameters and viral mutability in the progression of HIV-1 infection - Ortega, Horacio (Ciencia)
We use the concepts of immunodominance and antigenic oscillation for describing a model of HIV-1infection. We consider not only mutating virions and T-CD4 cells, but also viral reservoirs as macrophages and follicular dendritic cells (FDPC). We also consider strong cytotoxic attack against reservoirs and the extra cellular attack on virions, both coordinated by T-CD4 cells. We simulate mutations by a Montecarlo routine. Virus high mutability impairs the immune system by nullifying the assumed attack by immune cells (CTL) to infected reservoirs. Additionally our results show that tackling virus invasion and posterior output from reservoirs could be an important alternative in therapy.